Diffusion effects in nonlinear dynamics of hepatitis B virus. (12th July 2021) - Issa, S; Mbopda Tamko, B; Dabolé, B; Tabi, C B; Fouda Ekobena, H P
Abstract: A dynamic system of viral hepatitis B with healthy, infected cells and free virus is investigated in this work taking into account diffusion effects. The model is shown to be governed by a biological system of equations of prey-predation, competition and commensalism species. The existence of exact traveling waves solutions is established through the (G'/G) expansion method. To further understand the dynamic mechanism of hepatitis B virus infection, we get the Kink, Bright and Dark type profiles and rise out the influence of diffusion parameter on the localization and the amplitude of the solutions which permits us to improve and give more information on the transmission and control of the disease. Numerical simulations are done to give evidence that hepatitis B virus model can be studied by considering the mobility of three species scenarios and also, indicated which dynamic specie cell is more stable than the other.